Analisis Desain Kelembagaan Pengadaan Pegawai Pemerintah dengan Perjanjian Kerja (PPPK) Guru di Kabupaten Lumajang - Ahmad Zaki Fadlur Rohman; Ma’rifatul Khoiriyah (Pencerah, 2023)
The momentum formation of a new status in the staffing structure in Indonesia raises pro and contra, especially for the teaching profession. This is not surprising because it is accompanied by the discourse of eliminating the existence of honorary workers in November 2023. Even though until now the number of honorary workers has dominated compared to the ASN. This study aims to analyze the procurement of PPPK teachers carried out in Lumajang regency using the Institutional Analysis and Development (IAD) point of view. In this case it will be seen how the agenda is designed to attract as many teachers as possible. Methode Using a case study qualitative research method with data collection techniques through interviews and documentation. The results of the study show that PPPK procurement in Lumajang is running quite well. Succesfully implementing a Merit System so that the selected teachers are truly highly qualified and competent in their fields. It can be concluded the procurement of PPPK teachers has a structured and more objective implementation plan. However, there are still some things that needed improvement such as available formations and affirmation policies.